RABBITAX EQUIPMENT FOR ECO-RABBIT FARMING - Pohoretski, Янош (Biota. Human. Technology, 2023)
The purpose of the study. To highlight the principles of rabbit breeding using eco-technology, features and advantages of Rabbitax equipment for eco-rabbit breeding. Methodology. The research is based on materials obtained within the framework of equipment for ecological rabbit breeding since 2004. Specialized equipment was analyzed all technological materials starting from design to production of it. These data were compared with the company’s own results on rabbit keeping and breeding, as well as with the analytical materials presented in the monograph by G.A. Kotsyubenko (2013). The experience of more than 600 farming households in Ukraine and abroad that have used Rabbax Technology rabbit breeding and rearing technology was also taken into account. Scientific novelty. The concept of this eco-technology is based on the principles of a humane approach to rabbit breeding. These principles put the welfare of rabbits first, while not losing the profitability of the breeding business, rejecting the harsh exploitation of animals and the depletion of their bodies. In the eco-technology of rabbit breeding, special attention is paid to creating optimal conditions for the animals. This involves creating comfortable housing systems with proper ventilation, lighting, and temperature conditions. In addition, the eco-technology of rabbit breeding uses measures to protect animals from a wide range of harmful factors. For example, the equipment uses a system to prevent rabbits from being poisoned by harmful gases in living quarters, such as ammonia, hydrogen sulfide, methane and carbon dioxide, which are formed during the decomposition of rabbit waste. In addition, the equipment for rabbit breeding using eco-technology takes into account the innate needs that encourage animals to show their natural vitality, refraining from veterinary manipulations, which are usually abused to make a profit at any cost. This approach helps to meet the physiological and psychological needs of rabbits, which is an innovative approach to their maintenance and breeding. Conclusions. The use of humane rabbit-keeping technologies, in particular eco-technology from Rabbax Technology, is an effective and ethically acceptable approach for rabbit breeding. Eco-technology provides the best conditions for the development of rabbits in captivity, contributing to their health. Compared to techno-rabbit breeding, eco-technology has the advantage of preserving the physical and psychological condition of rabbits. It is worth noting that techno-rabbit breeding technology has an advantage in raising rabbits with regard to obtaining a larger weight (50 grams more), but with a significant disadvantage - a weak and ill organism. Thus, raising rabbits using ethically acceptable methods not only ensures the welfare of animals but also demonstrates its production feasibility, which is especially relevant in the modern economic environment.